Lipid profile alterations in Young Adults using Smokeless Tobacco: A prospective observational study from an urban center in Pakistan. - Farhan Haleem; Faisal Tahir; Syed Ali Jafri; M. Faizan Adil; Basit Mahesar; Sabir Ali; M. Ali Khan (International Journal of Endorsing Health Science Research, 2024)
Background: Smokeless tobacco (ST) use is a prevalent health concern in South Asia, with increasing consumption among young adults. While the association between smoking and cardiovascular diseases (CVDs) is well-documented, the impact of ST on lipid profiles and related cardiovascular risks remains underexplored. This study aims to assess the lipid parameters in young adult ST users to evaluate potential dyslipidemia and its implications for cardiovascular health. Methodology: This prospective observational study was conducted at Sindh Government Hospital Liaquatabad from November 2021 to April 2022. A total of 100 participants aged 18-30 years, who self-reported regular use of ST for at least 12 months and were non-smokers, were included. Lipid profiles, including total cholesterol, triglycerides, high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C), were measured after an overnight fast. Patients on lipid-altering medications or with significant comorbidities were excluded. Statistical analysis was performed using SPSS version 22.0. Results: The cohort predominantly consisted of young men (87%), with a mean age of 21.72 ± 3.66 years. Most participants were students (57%) and from low socioeconomic backgrounds (89%). Overall, lipid levels were generally within normal ranges, with the exception of low levels of HDL-C, which were particularly pronounced in women. In detail, the mean HDL-C for men was 41.55 ± 6.94 mg/dL, whereas women exhibited significantly lower HDL-C levels at 30.09 ± 5.94 mg/dL (p < 0.01). Other lipid parameters, including LDL-C, total cholesterol, and triglycerides, did not show significant elevations. Specifically, the mean LDL-C was 147.16 ± 3.60 mg/dL for men and 136.36 ± 9.96 mg/dL for women (p < 0.01), while total cholesterol levels averaged 125.70 ± 23.81 mg/dL for men and 124.55 ± 27.52 mg/dL for women (p = 0.882). Triglycerides were comparable between genders, with men at 131.21 ± 17.14 mg/dL and women at 131.91 ± 20.70 mg/dL (p = 0.902). Conclusion: This study found that while overall lipid levels were normal, female participants exhibited significantly low levels of HDL-C, indicating potential gender-specific cardiovascular risks.